Climate Change in Ethiopia Variability, Impact, Mitigation, and Adaptation - Zerga, Belay; Gebeyehu, Getaneh (IJRDO - Journal of Social Science and Humanities Research, 2016)
Climate change refers to long term fluctuations of temperature, precipitation, wind and other elements of Earth’s climate system. It is a change of climate which is attributed directly or indirectly to human activity that alters the composition of the global and/or regional atmosphere. Natural climate variability observed over comparable time periods in the types of changes of temperature and rainfall. It occurs because of internal variability within the climate system and external factors. The external causes may be natural or human induced activity. Human activities cause climate change mainly due to fossil fuel burning and removal of forests. Ethiopia’s contribution to GHG emissions is very low on a global scale. The emissions of greenhouse gases are predominantly from high-income countries while the negative effects of climate change are predominantly in low income countries. This means climate change is generally expected to hit developing countries harder than industrialized countries. Developing countries are less capable of mitigating or adapting to the changes due to their poverty and high dependence on the environment for subsistence. It has brought an escalating burden to already existing environmental concerns of the country mainly by anthropogenic factors. Climate change causes wide-ranging effects on the environment, socio-economic and related sectors, including water resources, agriculture and food security, human health, terrestrial ecosystems and biodiversity. Similarly, the mainstay of the Ethiopian economy is rain-fed agriculture, which is heavily sensitive to climate variability and change. In addition, many species with limited geographical opportunities, restricted habitat requirements and/or small populations are typically the most vulnerable. The Ethiopian Government has already put in place a number of policies, strategies and programs aimed at enhancing the adaptive capacity and reducing climate variability and change. Thus, the country’s Climate-Resilient Green Economy (CRGE) focuses on four pillars (namely agriculture, forestry, renewable energy, and advanced technologies) that will support Ethiopia’s developing green economy. Thus, this review paper tries to see climate change and its mitigation and adaptation efforts in Ethiopia.